EFEKTIVITAS MODEL PEMBELAJARAN TIPE KOOPERATIF TGT BERBANTUAN MEDIA FLIP CHART DAN LKS TEKA-TEKI SILANG TERHADAP HASIL BELAJAR SISWA KELAS IX DI SMP NEGERI 4 MAULIRU - Kareri Hara, Esi; Tamu Ina, Anita; Louise Makatita, Audrey (Universitas Cokroaminoto Palopo, 2024)
Based on the interview results obtained, it was found that the main problem in the study was low student learning outcomes, this was caused by teachers because they had not made changes to the learning models and media used. This study aims to determine how student learning outcomes at SMP Negeri 4 Mauliru are influenced by the cooperative learning model Team Games Tournament with the help of Flip Chart media and LKS Teka-Teki Silang. This study uses a quantitative approach. Experimental class, and IX A were used as control classes and IX B was used as experimental classes. Tests were conducted to collect data. Validity and reliability tests, descriptive analysis, normality and homogeneity tests and sample hypothesis tests and dependent samples were all conducted using SPSS. The pretest and posttest scores for the experimental class averaged 56.57 and 74.71 while the pretest and posttest scores for the control class averaged 46.35 and 67.28. Hypothesis testing conducted showed a significant effect indicated by the Asymp Sig (2-tailed) value of 0.001, which means less than 0.05. Thus, the use of cooperative learning model of Team Games Tournament type assisted by Flip Chart media and LKS Crossword Puzzle, has an impact on the learning achievement of class IX B students at SMP Negeri 4 Mauliru. Keywords: TGT Model, Flip Chart, LKS Crossword Puzzle, learning outcomes.